PENGARUH MOTIVASI EKONOMI DAN MOTIVASI SOSIAL DALAM MENDORONG GENERASI MUDA MEMULAI USAHA - Delfira, Asyifah Fauzah; Ramadani, Suci; Monica, Peby; Ramadhani, Dilla Amelia; Yuliarman, Putri (Fakultas Ekonomi Universitas Negeri Medan, 2024)
The younger generation starts businesses with a strong drive from economic motivation and social motivation, with this drive making them innovate and contribute through the business they run. This article aims to look at the influence of economic motivation and social motivation on the younger generation in starting a business. This study uses a quantitative approach. The data collection technique was through the distribution of questionnaires through google from 50 respondents. The results of this study can be concluded that the variable of economic motivation is more dominant in influencing the younger generation to start a business. Keywords: Economic Motivation, Social Motivation, Starting a Business